Application of Interpersonal Communication To Improve Employee Motivation at PT. Rifansi Dwi Putra - Doini , Syafri (LSPR Institute of Communication & Business, 2022)
Communication is important in the activities of every human group because through communication a mutual understanding between certain parties and other parties is created, while also increasing harmony and coordinating various different activities or tasks. PT. Rifansi Dwi Putra in Duri District, Riau was established in 1997, where it has growth from local companies in Riau to become one of the national companies that achieved impressive service records in the oil and gas industry, especially around the operations of PT. Chevron Pacific Indonesia. The research method used is a qualitative research method that emphasizes in-depth interviews with respondents who have experience in their respective fields of work. Among them are five members of the company, consisting of Admin Ops Transport, Foreman, Swamper, and two Drivers. Effective interpersonal communication should be able to create effective interpersonal relationships that can motivate a conducive employee performance at PT. Rifansi Dwi Putra, Duri District, Riau, so that they have to improve and continue to develop good communication systems to be more effective.